The Impact Of Socio-Economic Characteristics on Settlement Quality - Hidayati, Inayah (geoedusains: Jurnal Pendidikan Geografi, 2021)
This research explains the impact of socio-economic characteristics on settlement quality. The socio-economic factor deals with the respondents’ background. It covers the family head’s education, dependents, and family income. The present study applied mixed methods with survey and observation The result of the study showed that education constitutes one of the indicators of the human development index. The number of dependents concerns the number of individuals whose needs are satisfied by the family head. A dependent may live with the family in one house, or live in a different place. The variable of household income refers to not only the combination of the husband and wife's income but also that of all members of the family. This study confirmed that the majority of the household’s income is less than one million rupiahs because most of the farmer households do not own fields.